Characterization of ambarella (Spondias dulcis) genotypes based on morphological and physio-biochemical quality attributes - DEVI, M P; SINGH, S R; SINGH, R K D; CHANCHAN, M; KHANGJARAKPAM, G (The Indian Journal of Agricultural Sciences, 2024)
Survey and characterization of ambarella found in valley region of Manipur was conducted during 2022–23 to identified superior genotypes for yield and various physio-biochemical characters having sweeter taste and high yield traits. Genotype P7 gave maximum yield (147.10 kg/tree) and P19 has maximum fruit weight (158.50 g), length (7.09 cm) and width (6.65 cm). However, genotypes P17 has highest TSS (170Brix), total sugar (6.84%), P7 highest vitamin C (40.81 mg/100 g) and P19 gave highest vitamin A content (0.62 mg/100 g). Hence, genetic diversity of ambarella was observed among the selected genotypes in valley region of Manipur for screening elite genotypes for the future.